from lean manufacturing to smart factory: communication in the work organization processes in the capit - Nociolini Rebechi, Claudia (2020)
This article aims to reflect on communication in flexible labor management through a discussion that dialogues with critical studies on the new forms of labor exploitation in current capitalism. More specifically, we seek to address ways of mobilizing communication in support of the organizational logic of work assumed by companies that consider themselves flexible and lean, or smart. The main focus is on the critical examination of the constitutive elements of a particular narrative, present in the contemporary world of work, which combines technological transformations and the precariousness of human labour.